Analysis of the Role of Parents in Online Learning in the Covid-19 Pandemic - Etty Yusrika Fitri; Johannis Siahaya; Alifian Nugraha; Ilham Arief (HK-Publishing, 2022)
AbstractDuring the Covid-19 pandemic in Indonesia, the learning system in schools offline was changed to an online learning system, commonly called Distance Learning. This online learning not only involves educators and students but also involves parents. Because parents directly accompany their children while studying at home. For this reason, there is a need for assistance from parents to children in the online learning process. But of course, there are several positive and negative causes in this online learning process. Because the things parents feel are different, students and educators are foreign. Some feel effective with, and some feel less effective with this online learning.Keywords: Role o f Parents, Online Learning, Covid-19 Pandemic AbstrakDi masa pandemi Covid-19 di Indonesia, sistem pembelajaran di sekolah offline diubah menjadi sistem pembelajaran online yang biasa disebut Pembelajaran Jarak Jauh. Pembelajaran online ini tidak hanya melibatkan pendidik dan siswa tetapi juga melibatkan orang tua. Karena orang tua langsung mendampingi anaknya selama belajar di rumah. Untuk itu perlu adanya pendampingan dari orang tua kepada anak dalam proses pembelajaran online. Namun tentunya ada beberapa penyebab positif dan negatif dalam proses pembelajaran online ini. Karena hal yang dirasakan orang tua berbeda, siswa dan pendidik menjadi asing. Ada yang merasa efektif dengan, dan ada yang merasa kurang efektif dengan pembelajaran online ini.Kata kunci: Peran Orang Tua, Pembelajaran Online, Pandemi Covid-19